Dietary Bacillus licheniformis shapes the foregut microbiota, improving nutrient digestibility and intestinal health in broiler chickens - Han, Yunsheng; Xu, Xin; Wang, Jiaxin; Cai, Hongying; Li, Daojie; Zhang, Hongwei; Yang, Peilong; Meng, Kun (Frontiers in Microbiology, 2023)
Bacillus licheniformis is considered a potential alternative to antibiotic growth promoters of animal growth and health. However, the effects of Bacillus licheniformis on the foregut and hindgut microbiota, and their relationships with nutrient digestion and health, in broiler chickens remain unclear. In this study, we aimed to identify the effects of Bacillus licheniformis BCG on intestinal digestion and absorption, tight junctions, inflammation, and the fore- and hind-gut microbiota. We randomly assigned 240 1-day-old male AA broilers into three treatment groups: CT (basal diet), BCG1 (basal diet + 1.0 × 108 CFU/kg B. licheniformis BCG), and BCG2 (basal diet + 1.0 × 109 CFU/kg B. licheniformis BCG). Compared with the CT group, the B. licheniformis BCG group showed significantly greater jejunal and ileal α-amylase, maltase, and sucrase activity; moreover, the α-amylase activity in the BCG2 group was higher than that in the BCG1 group (P < 0.05). The transcript abundance of FABP-1 and FATP-1 in the BCG2 group was significantly greater than that in the CT and BCG1 groups, and the GLUT-2 and LAT-1 relative mRNA levels were greater in the BCG2 group than the CT group (P < 0.05). Dietary B. licheniformis BCG resulted in significantly higher ileal occludin, and lower IL-8 and TLR-4 mRNA levels than observed in the CT group (P < 0.05). B. licheniformis BCG supplementation significantly decreased bacterial community richness and diversity in the ileum (P < 0.05). Dietary B. licheniformis BCG shaped the ileac microbiota by increasing the prevalence of f_Sphingomonadaceae, Sphingomonas, and Limosilactobacillus, and contributed to nutrient digestion and absorption; moreover, it enhanced the intestinal barrier by increasing the prevalence of f_Lactobacillaceae, Lactobacillus, and Limosilactobacillus. Dietary B. licheniformis BCG decreased microbial community diversity by diminishing Desulfovibrio, Alistipes, Campylobacter, Vibrio, Streptococcus, and Escherichia coli-Shigella levels, and down-regulating inflammatory associated molecule expression. Therefore, dietary B. licheniformis BCG contributed to digestion and absorption of nutrients, enhanced the intestinal physical barrier, and decreased intestinal inflammation in broilers by decreasing microbial diversity and optimizing the microbiota structure.